2016
DOI: 10.1177/1352458516671819
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing increase in incidence and prevalence of multiple sclerosis in Newcastle, Australia: A 50-year study

Abstract: Prevalence of MS in Newcastle has risen linearly and is contributed to by a substantial increase in new cases over the preceding decade. Female predominance of MS cases continues to increase with a new diagnosis three times more likely in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 24 publications
7
47
0
Order By: Relevance
“…The average age at diagnosis was 40 years amongst the whole cohort (combined relapse onset MS/PPMS), comparable to that reported in the UK (Mackenzie et al, 2014), Australia (Ribbons et al, 2016) and Canada (Kingwell et al, 2015;Marrie et al, 2013). This is at the upper limit of the traditionally reported 20-40 year age range (Compston and Coles, 2008).…”
Section: Discussionsupporting
confidence: 75%
“…The average age at diagnosis was 40 years amongst the whole cohort (combined relapse onset MS/PPMS), comparable to that reported in the UK (Mackenzie et al, 2014), Australia (Ribbons et al, 2016) and Canada (Kingwell et al, 2015;Marrie et al, 2013). This is at the upper limit of the traditionally reported 20-40 year age range (Compston and Coles, 2008).…”
Section: Discussionsupporting
confidence: 75%
“…The variable magnitude of MS risk in 2 age ranges of population in Kuwait has also been previously documented [6, 7, 26]. A recent report of an ongoing increase in MS burden over 50 years period in Newcastle, Australia, also discerned similar age-specific bimodal patterns (at-onset) in MS incidence during 1986–2011 [27]. We are unaware of any study that reported such bimodality in age-specific MS risk based on APC analysis.…”
Section: Discussionmentioning
confidence: 57%
“…More recently, and when consistent means of identifying MS are applied, MS incidence has not increased in several locations, such as in the Canadian provinces of British Columbia (1996-2008) [10], Manitoba (1998Manitoba ( -2006 [11] and Nova Scotia (1990-2010) [12], as well as Western Norway [13] and the UK (1990-2010) [14]. There has been an apparent increase in other locations, such as Newcastle, Australia [9], although, again, this is a study within a small population (in 2011 the general population totalled 148 535) and with a small number of cases, particularly historically. We do not seek to fully review the incidence of MS worldwide, but to highlight that secular trends in MS are variable across countries, and that ascertainment and instability of estimates due to small numbers of people with MS still threaten the validity of estimates.…”
Section: Discussionmentioning
confidence: 99%